How Light‐Absorbing Properties of Organic Aerosol Modify the Asian Summer Monsoon Rainfall?. Issue 4 (22nd February 2018) - Chu, Jung‐Eun; Kim, Kyu‐Myong; Lau, William K. M.; Ha, Kyung‐Ja
Abstract: Light‐absorbing aerosols not only contribute to Earth's radiative balance but also influence regional climate by cooling the surface and warming the atmosphere. Following recent suggestions that organic aerosols (OAs) absorb substantial amount of solar radiation, we examine the role of light‐absorbing properties of OA on Asian summer monsoon rainfall redistribution using observational data and an atmospheric general circulation model experiment. Results suggest that the enhanced light absorption by OA in Southeast Asia and Northeast Asia is associated with the advance of the Indian summer monsoon in May and the southward shift of East Asian summer monsoon rainband in June. The rainfall redistribution in May is induced by elevated orographic effect with a warm‐core upper‐level anticyclone and surface warming of 1–2 °C over the Tibetan Plateau, whereas that of the East Asian summer monsoon in June is formed by stable conditions associated with surface cooling and atmospheric warming around 30°N. Key Points: Impact of enhanced OA light absorption on Asian summer monsoon is examined using observations and an AGCM experiment OA light absorption acts to advance the Indian summer monsoon and shift East Asian summer monsoon rainband southward The effects of OA light absorption in aerosol‐monsoon interaction can be substantial and cannot be ignored